Prevalence of back pain in a group of elite athletes exposed to repetitive overhead activity - Fett, D.; Trompeter, K.; Platen, P. (PLOS ONE, 2019)
Background: The prevalence of back pain in athletes has been investigated in several studies, but there are still under- or uninvestigated sports discipline like sports exposed to repetitive overhead activity. Elite athletes spend much time in training and competition and, because of the nature of their disciplines, subject their bodies to a great deal of mechanical strain, which puts a high level of stress on their musculoskeletal systems. From this it is hypothesized that elite athletes who engage in repetitive overhead motions experience a higher strain on their spine and thus possibly a higher prevalence of back pain compared with an active control group.